PERSEPSI WARGA UNIVERSITI MALAYA TERHADAP NASIHAT UNTUK ‘TIDAK IKUT SERTA’ DALAM SAMBUTAN BON ODORI DI MALAYSIA - Jamaludin, Nor Asyikin; Hassan, Asmadi (WILAYAH: The International Journal of East Asian Studies, 2023)
This study focuses on the perception of University of Malaya community towards the advice given by religious minister and agencies to the muslim community to ’not participate’ in the Bon Odori festival organized in Malaysia. The objectives of this study are divided into three which are to find out the Bon Odori festival according to the beliefs of the Japanese community, to identify the main factors caused the muslims in Malaysia to be advised not to participate in the Bon Odori and to evaluate the perception of Universiti Malaya community towards the advice given. The research method used is a quantitative. The researchers conducted a questionnaire survey on 200 University of Malaya communities. Data were analyzed using the Statistical Package for Social Sciences (SPSS) software. The findings of this study were the respondents had different views on the advice received by muslims. However, the majority of Universiti Malaya community accepted the Bon Odori festival and they also felt that the advice given by the relegious authorithy to Muslims was appropriate. Ultimately, it is hoped that this study can help researchers and readers understand current issues, and understand the level of acceptance of a society towards the Bon Odori.